DETERMINE EFFECTIVENESS OF POLY-VINYLPYRROLIDONE (PVP) AS KINETIC HYDRATE INHIDITORS USING DSC - ROZALI, MUHAMMAD IRSYADUDDIN (Universiti Teknologi PETRONAS, 2011)
Gas hydrates can form in both gas-producing and oil-producing wells, which can cause hazardous problems such as pipeline clogging and hydrates agglomeration. Gas hydrates is favorable in conditions of low temperature (0°C - l5°C) and high pressure (>600psia) in presence of natural gas and water in the form of vapor or moisture. In this condition, crystalline structures (gas hydrates) is formed. Hydrates plug have been serious economic concern in oil and gas production pipelines and affect flow assurance as well. The presence of gas hydrates in pipelines is causing serious operational problem and safety problems. Kinetic hydrate inhibitors (KHis) are injected in order to delay the nucleation of hydrates within the residence time. The effectiveness of KHI is examined on the four different samples of water-in-oil emulsion by using Differential Scanning Calorimetry (DSC). Heat transfer is measured by DSC in different concentration of poly-vinylpyrrolidone (PVP) used as kinetic hydrate inhibitor. The result shows that sample with 0.7wt% of PVP is observed to be the most effective at delaying the hydrate formation time. Therefore, PVP can be considered to be applied as kinetic hydrate inhibitor in the oil and gas industry instead of conventional method, Thermodynamic Hydrate Inhibitor (THI) since KHI is used at low concentration thus it is cheaper and environmental friendly product.